Abstracts of reports made in the young people scientific and technical festival of the western administrative district - Editorial Article (Тонкие химические технологии, 2011)
On the 29th of May The Young People Scientific and Technical Festival took place in M.V. Lomonosov Moscow State Academy of Fine Chemical Technology. The Festival was sponsored by the authorities of the Western Administrative District (WAD) and the Moscow Family and Youth Policy Department. The main aim of the Festival was to bring to light the topical research on various subjects. It also helped to stimulate and develop the further scientific research carried out by students, postgraduates and young scientists from institutes and universities, lyceums and schools. The researches were represented by students from M.V. Lomonosov Moscow State Academy of Fine Chemical Technology, M.V. Lomonosov MSU, MIREI, MAMI, Lavochkin FSUE SPA, AWSR, MESI, SEE UYT «Solntsevo», Khrunichev SCSPC.